THE QUALITY OF LIFE (QOL) AMONG SURVIVORS OF SEXUAL ASSAULT – A DESCRIPTIVE STUDY IN A MEDICAL COLLEGE OF KOLKATA (Journal of Forensic Medicine & Toxicology, 2024)
Introduction- Sexual harassment and assault are arguably the most odious crimes done to the human body. Almost 25% of the female population experience sexual violence by an intimate partner, and up to one-third of girls before adulthood report their first sexual experience as being a forceful one. It directly degrades the quality of life (QOL) by hampering self-perception, self-realization, daily living and activities, and family and social life. Methodology- This study was conducted on the survivors of sexual assault attending the Department of Forensic Medicine and Toxicology for the medicolegal examination in Kolkata. Demographic parameters and WHOQOL_BREF were used for assessing the QOL in the survivors. Results- A total of 25 cases aged 19 to 58 years were included. Almost all the survivors showed poor scores in the components of physical health, psychological health, social relationships, and environment. Statistically significant correlation was present between all the domains except psychological health and social relationship domain, and psychological health and environment domain. Conclusion- Studies have proved the deleterious effects of sexual trauma in childhood or adult age on psychological and physical distress. Studies have proved already that female survivors of severe sexual trauma in childhood or adult age may experience psychological and physical distress in the long term.
Keywords: Quality of Life; Sexual assault; Sexual offence; Survivors; WHO